PEMUTUAN TENAGA KEPENDIDIKAN DALAM MENGHADAPI TANTANGAN ERA GLOBALISASI - Lobud, Sjakir (State Institute of Islamic Studies (IAIN) Palu, 2007)
The Era of globalization with its challenges have to be faced with conceptual, systematical and implementation efforts. Therefore, in the case of education, one of efforts should be taken to face the era of globalization is through the enhancement of education quality. Based on this, educators, both lecturers and teachers have to possess a good competence and profesional skill in managing educationÂ Kata Kunci: Pemutuan tenaga pendidikan, tantangan globalisasi